Investigating the Participation of Female Software Developers in Retrospective Meetings - Galeno, Larissa; Mota, Wesley; Mello, Rafael de (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2024: Anais do IX Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software, 2024)
Retrospective meetings represent a crucial SCRUM event for software development teams to reflect and identify directions for improving collaboration and performance for the sprint. For this, professionals should feel comfortable and in a favourable environment to express their thoughts and be heard. In this paper, we report an interview-based study conducted with eight female software developers aiming to understand participation in retrospective meetings and how this affects their experience in the work environment in which they are inserted. Despite being identified with their teams and recognizing the promotion of gender diversity in their company, we found that they diverge in feeling comfortable expressing their thoughts.